2015
DOI: 10.1590/0103-8478cr20141284
|View full text |Cite
|
Sign up to set email alerts
|

Endodontics pastes formulated with copaiba oil: action on oral microbiota and dentin bridge formation in dogs

Abstract: This study analysed the effect of pastes formulated with calcium hydroxide P.A. and different vehicles (saline solution -paste A and Copaifera langsdorffii Desfon oil -paste B) on oral microorganisms and dentin bridge formation in dogs. The antimicrobial action of the pastes and their components was analysed by the minimum inhibitory concentration in agar gel RESUMO Foi avaliada a ação de pastas formuladas com hidróxido de cálcio P.A. e diferentes veículos (solução fisiológica -pasta A e óleo de Copaifera lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Copaiba oil, regardless of its genus, presented results of bactericidal and/or bacteriostatic effect. The most studied microorganisms against copaiba in this systematic review were Streptococcus mutans (Bardají et al, 2016;Bari et al, 2016;Conde et al, 2015;da Silva Moraes et al, 2016;Dias et al, 2015;Pieri et al, 2010;Pieri et al, 2012;Simões et al, 2016;Vasconcelos et al, 2008) followed by Streptococcus sanguinis (Bardají et al, 2016;da Silva Moraes et al, 2016;Simões et al, 2016;Vasconcelos et al, 2008), Streptococcus sobrinus (Bardají et al, 2016;Conde et al, 2015;da Silva Moraes et al, 2016;, Fusobacterium nucleatum (Bardají et al, 2016;, . Only one study demonstrated that copaiba oil presented antimicrobial effect similar or superior to the positive control used (Pieri et al, 2010).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Copaiba oil, regardless of its genus, presented results of bactericidal and/or bacteriostatic effect. The most studied microorganisms against copaiba in this systematic review were Streptococcus mutans (Bardají et al, 2016;Bari et al, 2016;Conde et al, 2015;da Silva Moraes et al, 2016;Dias et al, 2015;Pieri et al, 2010;Pieri et al, 2012;Simões et al, 2016;Vasconcelos et al, 2008) followed by Streptococcus sanguinis (Bardají et al, 2016;da Silva Moraes et al, 2016;Simões et al, 2016;Vasconcelos et al, 2008), Streptococcus sobrinus (Bardají et al, 2016;Conde et al, 2015;da Silva Moraes et al, 2016;, Fusobacterium nucleatum (Bardají et al, 2016;, . Only one study demonstrated that copaiba oil presented antimicrobial effect similar or superior to the positive control used (Pieri et al, 2010).…”
Section: Resultsmentioning
confidence: 97%
“…It was observed in this analysis that all studies presented an unclear risk of bias for randomization, allocation concealment, and blinding of the evaluators. Hence, appropriate statistical analysis was performed only in five of the 11 featured items (Bardají et al , ; Bari et al , ; Dias et al , ; Pieri et al , ; Simões et al , ). In addition, in two other articles, the statistical analysis is not clear (Souza et al, ; Souza et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Já no experimento de Dias-da-Silva et al (2013) observou-se um efeito benéfico no uso desse produto em alvéolo dentário na cicatrização do osso, nas administrações tópica e sistêmica, causando, porém, efeitos deletérios em tecido conectivo. Ainda sobre o uso de copaíba em odontologia veterinária, Dias et al (2015) constataram que o uso de pasta de hidróxido de cálcio P. A. associada à óleo de copaíba não apresentou diferenças, quando comparada ao padrão (associação da pasta com solução salina estéril), tendo ambas os mesmos resultados sobre a formação de ponte dentária, além de apresentarem efeito antimicrobiano semelhantes.…”
Section: A Copaíba Como Agente Cicatrizanteunclassified